2013
DOI: 10.1371/journal.pone.0062922
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Buds and Leaves Using 454 Pyrosequencing to Discover Genes Associated with the Biosynthesis of Active Ingredients in Lonicera japonica Thunb.

Abstract: Background Lonicera japonica Thunb. is a plant used in traditional Chinese medicine known for its anti-inflammatory, anti-oxidative, anti-carcinogenic, and antiviral pharmacological properties. The major active secondary metabolites of this plant are chlorogenic acid (CGA) and luteoloside. While the biosynthetic pathways of these metabolites are relatively well known, the genetic information available for this species, especially the biosynthetic pathways of its active ingredients, is limited.Methodology/Princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 75 publications
0
53
0
1
Order By: Relevance
“…Lonicera japonica Thunb, also known as Japanese honeysuckle, 'Jin Yin Hua', and 'Ren Dong', belongs to the Caprifoliaceae family and is often used in traditional Chinese and Japanese medicine [1]. L. japonica is native to eastern Asia, and is cultivated worldwide, particularly in China, Japan, and Korea due to its medicinal properties, and as an ornamental plant due to its pleasant smelling flowers, and attractive evergreen foliage [2]. However, as it is highly invasive to the ecology of some countries, such as New Zealand and several other countries including North America, it is considered a major nuisance and is restricted [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lonicera japonica Thunb, also known as Japanese honeysuckle, 'Jin Yin Hua', and 'Ren Dong', belongs to the Caprifoliaceae family and is often used in traditional Chinese and Japanese medicine [1]. L. japonica is native to eastern Asia, and is cultivated worldwide, particularly in China, Japan, and Korea due to its medicinal properties, and as an ornamental plant due to its pleasant smelling flowers, and attractive evergreen foliage [2]. However, as it is highly invasive to the ecology of some countries, such as New Zealand and several other countries including North America, it is considered a major nuisance and is restricted [3].…”
Section: Introductionmentioning
confidence: 99%
“…L. japonica has been used as traditional medicine in China for over thousands of years, and has been listed as top grade in 'Ming Yi Bie Lu' and 'Shen Nong Ben Cao Jing', and described in 'Ben Cao Gang Mu', the famous classical book of Chinese Materia Medica, as early as the seventeenth century, for applications in various diseases such as to clean away the heat-evil or heal the swelling [1]. Different parts of L. japonica have been reported to possess unique medicinal properties, with flowers and floral buds being highly used in Chinese traditional medicine, while the leaves and stems are used in Japan [2,4,5]. The commercial value of L. japonica in the herbal medicine trading market has increased by several hundred-fold in recent years, and [30 % of current traditional Chinese medicine prescriptions contain extracts from different plant parts of L. japonica [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, traditional phytotherapy and plant‐derived natural medicine are quite popular for treating liver diseases. Lonicera japonica Thunb (Caprifoliaceae family), known as Jinyinhua (in Chinese), is widely consumed as healthy tea beverage and used in traditional Chinese medicine (TCM) to treat various diseases including hepatitis, arthritis, allergy and infection . Of particular interest is the L. japonica ‐containing TCM formula: Yin‐zhi‐huang (YZH) is a classical polyherbal prescription dated from the traditional Chinese prescription ‘Yin‐chen‐hao‐tang’, which has been widely used in East Asian countries for more than a thousand years to treat jaundice and chronic liver diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the L. japonica ‐containing TCM formula: Yin‐zhi‐huang (YZH) is a classical polyherbal prescription dated from the traditional Chinese prescription ‘Yin‐chen‐hao‐tang’, which has been widely used in East Asian countries for more than a thousand years to treat jaundice and chronic liver diseases . Extensive studies on the phytochemical ingredients from coffee and L. japonica demonstrated that chlorogenic acid (CGA) is supposed to be the primary active component (indicator compound) contributing to the health benefits …”
Section: Introductionmentioning
confidence: 99%